Mechanisms of embodiment - Dijkstra, Katinka; Post, Lysanne (Frontiers in Psychology, 2015)
This paper is a critical review of recent studies demonstrating the mechanism of sensorimotor simulation in different cognitive domains. Empirical studies that specify conditions under which embodiment occurs in different domains will be discussed and evaluated. Examples of relevant domains are language comprehension (Tucker & Ellis, 2004), autobiographical memory (Dijkstra, Kaschak, & Zwaan, 2007), gestures (Alibali, Boncoddo, & Hostetter, 2014), facial mimicry (Stel & Vonk, 2010), and problem solving (Wiemers, Bekkering, & Lindemann, 2014). The focus of the review is on supporting claims regarding sensorimotor simulation as well as on factors that modulate dynamic relationships between sensorimotor components in action and cognitive domains, such as expertise (Boschker, Bakker, & Michaels, 2002). This discussion takes place within the context of currently debated issues, specifically the need to specify the underlying mechanisms of embodied representations (Zwaan, 2014; Körner, Topolinski, & Strack, 2015).